Mechanisms of the Implied Reader in al-Jahiz’s Epistle The Preference of Speech over Silence in Light of Reception Theory - Al-Huweirini, Amal Bint Abdullah Bin Ali (Arts for Linguistic & Literary Studies, 2025)
This study investigates the mechanisms of the implied reader in al-Jahiz’s epistle The Preference of Speech over Silence through the lens of Reception Theory. After introducing the epistle and outlining Wolfgang Iser’s concept of the implied reader, the research analyzes selected mechanisms that shape the reader’s interaction with the text. On the formal level, it focuses on linguistic, rhetorical, and stylistic devices—such as sajʿ (rhymed prose), allusion, and other embellishments—which create interpretive gaps that the implied reader actively fills while engaging with the author’s ideas. On the semantic level, the study explores religious, social, and psychological dimensions that guide the implied reader toward deeper comprehension and foster responsive interaction with the text. The findings reveal that al-Jahiz consistently demonstrates respect for the recipient by diversifying his rhetorical and linguistic techniques to ensure sustained engagement. They also highlight his attentiveness to the cultural, religious, and psychological contexts of his readers, which allowed him to present his arguments in a compelling style that secures continuous reader involvement and directs the interpretation of his central message.